Electroluminescence from Organometallic Lead Halide Perovskite‐Conjugated Polymer Diodes. (19th February 2015) - Sadhanala, Aditya; Kumar, Abhishek; Pathak, Sandeep; Rao, Akshay; Steiner, Ullrich; Greenham, Neil C.; Snaith, Henry J.; Friend, Richard H.
<x xml:space="preserve">Abstract</x> Organometallic lead perovskite‐based solar cells can be converted to light‐emitting diodes by engineering the current density. Diodes are fabricated with adjacent perovskite and conjugated polymer layers using orthogonal solvents. Under forward bias, these devices show simultaneous emission from both the luminescent conjugated polymer and the perovskite, providing direct information on electron and hole recombination as a function of device architecture and bias voltage. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>